The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2139/ssrn.1489906
|View full text |Cite
|
Sign up to set email alerts
|

The Ins and Outs of Dualisation: A Literature Review

Abstract: The Working Papers on the Reconciliation of Work and Welfare in Europe series seeks to promote the diffusion of research and research integration activities taking place within the network and being produced by other researchers working on issues of work and welfare in Europe. Working papers are published either within the framework of a series of closed calls, which follow the different stages in the life-cycle of the network's activities, or as part of an open call, which aims to privilege both research focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 8 publications
0
32
0
Order By: Relevance
“…The main idea behind dual labor market theory (e.g., Doeringer & Piore, ; Lindbeck & Snower, ) is that labor markets are divided into primary and secondary sectors, with limited mobility between the two (see Davidsson & Naczyk, ). The main purposes of this division is to keep a primary workforce that secures the core skills of the company, while relying on the secondary market to adjust to cyclical demands and fluctuations.…”
Section: Theorymentioning
confidence: 99%
“…The main idea behind dual labor market theory (e.g., Doeringer & Piore, ; Lindbeck & Snower, ) is that labor markets are divided into primary and secondary sectors, with limited mobility between the two (see Davidsson & Naczyk, ). The main purposes of this division is to keep a primary workforce that secures the core skills of the company, while relying on the secondary market to adjust to cyclical demands and fluctuations.…”
Section: Theorymentioning
confidence: 99%
“…The main idea behind dual labour market theory (e.g, Doeringer and Piore, 1975;Lindbeck and Snower, 1989) is that labour markets are divided into primary and secondary sectors, with limited chance for mobility between the two (see Davidsson and Naczyk, 2009). …”
Section: Labour Market Dualization and Insiders And Outsidersmentioning
confidence: 99%
“…Recent literatures on the 'dualisation' of societies have suggested that as the distribution and coverage of social programmes have deteriorated, recent welfare states reforms have perpetuated the structures of advantage and disadvantage in the labour market, and contributed to a politics that enforces divides between 'insiders' and 'outsiders' (Davidsson and Naczyk 2009;Palier and Thelen 2010). The evidence here suggests that public sector 'modernization', 'marketization', and reform is having similar political consequences.…”
Section: Resultsmentioning
confidence: 70%
“…However, if British literatures have begun to move these debates forward, existing comparative welfare research has not yet analyzed these reversals in public sector services and employment, instead focusing primarily on spending, governance, and policy reform. The most recent current of welfare state research on 'Dualisation' has added to our knowledge about public policy changes and their political causes and political impacts by exploring how mean-testing and private provision arrangements are institutionalizing economic inequality throughout Western Europe (Davidsson and Naczyk 2009;Palier and Thelen 2010;). But it too says little about how public employment and public sector collective bargaining arrangements have themselves been overhauled and reworked as part of broader trends intended to lower labour costs.…”
Section: Mots-clésmentioning
confidence: 99%